The diaspora of Filipino teachers leaving their home country for work in the United States - Oca, Joan B. De; Malaga, Ronora S. (Edelweiss Applied Science and Technology, 2025)
This study aimed to investigate the Filipino public school teachers' diaspora to the United States, focusing on the factors influencing their migration and the challenges they encountered in adapting to their new environments. To achieve this, a parallel convergent mixed-methods approach was employed. The study conducted qualitative interviews with five participants and surveyed 69 former DepEd teachers across various states in the United States, covering the academic years 2018–2019 to 2023–2024. The results showed that the main motivators were improved living conditions and higher income. They also acknowledged difficulties with personal sacrifices, student conduct, and cultural adjustment. Teachers who were relocating encountered many challenges that required resilience, even though they had access to better resources. As systemic constraints in the Philippines drive highly trained instructors abroad, the study highlights a global education dilemma. It is, therefore, essential to strengthen institutional support and policy coordination to ensure that teacher migration remains a choice rather than a necessity in order to preserve the Philippine educational system and the well-being of its instructors overseas.